RISK ASSESSMENT KECELAKAAN KERJA PADA PENGOPERASIAN BOILER DI PT. INDONESIA POWER UNIT PEMBANGKITAN SEMARANG - Eliza Marceliana Zeinda; Sho’im Hidayat (Universitas Airlangga, 2016)
Boiler is a tool produced steam. The operation of boiler produce hazard that can cause accidents in labor. The purpose of this research is to risk assessment for accidents work in the operation of boilers in PT. Indonesia Power Unit Pembangkitan Semarang. This research is observational. The object of this research is boiler. The subject of this research is coordinator and operator boiler. The primary data was obtained from observation and interview, while secondary data from the corporate documents. The result showed that boilers in PT. Indonesia Power Unit Pembangkitan Semarang were 3 unit of water tube using fuel MFO and HSD. The identification hazard obtained 12 findings hazard on 9 areas the operation boiler PT. Indonesia Power unit Pembangkitan Semarang. The hazard in the area of boiler are noise, hot weather, fire sparks, hit, pinched hand, discover water vapor, high pressure, electricity, contact with a steam pipe, amount of oil, exposed NaOH liquid, and slip and fall down from the height. On controlling value, there were 6 hazards that classified as in very good control, 3 hazards were classified as partly implemented, and 3 hazards were classified as implemented. The residual risk was obtained 5 category risk with no risk and 7 risk categories low. Conclusion that can be drawn are hazard boiler in PT. Indonesia Power Unit Pembangkitan Semarang have high risk of are hazard discover water vapor and the high pressure. The company suggested to perform maintenance and reduce the risk to a low.Keywords: risk assessment, work accidents, boiler